Evaluation of the performance of two strains of Nile tilapia (Oreochromis Niloticus) in mixed raising systems - Neves,Patrícia Ribeiro (2008)
The aim of this study was to evaluate the productive performance of two strains of Nile tilapia (Oreochromis niloticus) in mixed raising systems. A total of 3600 fish-larvae species was used, 1800 belonging to Bouaké lineage, and 1800 to Chitralada. The experiment was carried out in three phases; Phase I in an incubator in 18 boxes, in which two treatments (Bouaké and Chitralada) were tested by using nine repetitions; Phases II and III were performed in 18 cement tanks with the same treatments. In phase I, regarding the final weight and gain of weight, Chitralada strain showed the highest final weight values. In phase II, Chitralada showed the highest final weight value when compared with Bouaké, and, considering the gain of weight, Bouaké obtained the best result. In phase III, Chitralada showed better final weight results (104 days of raising), final weight, final length and gain of length/cm (152 days of raising); but, after 279 days of the cultivation, Bouaké showed a higher weight and length gain. These findings showed that Chitralada strain presented the best performance.